Mental development of children from paired mothers with epilepsy: assessing remote teratogenic effects and predictors of developmental disorders - N. F. Mikhailova; A. S. Krasko; G. V. Odintsova; I. V. Larina; V. A. Mikhailov (Эпилепсия и пароксизмальные состояния, 2021)
Objective: to study teratogenic effect – the long-term pregnant mother-taken antiepileptic drugs (AEDs) related consequences on paired child mental, social and intellectual development.Material and methods. There were enrolled 80 subjects: 40 children aged 3–9 years and paired mothers suffering from epilepsy for 3 to 35 years. Thirteen and 27 patients had generalized and focal epilepsy, respectively. Seven mothers were in prolonged remission without taking AEDs, 23 were on monotherapy and 10 were on polytherapy. Child research methods: T. Achenbach's clinical CBCL (The Child Behavior Checklist) scales (for children aged under 5 and 6–18 years), a questionnaire for detecting attention deficit hyperactivity disorder and other behavioral disorders modified by N.N. Zavadenko, Wechsler Intelligence Scale for Children (WISC), Luria batteries of neuropsychological tests adapted by J.M. Glozman (for children aged 3–6 and 7–12 years).Results. Neuropsychological study and assessment of intelligence revealed problems in the development of praxis, speech, gnostic functions and memory, as well as disproportion in the development of verbal and non-verbal structures of intelligence. The most common behavioral disorders in children were impulsivity, distraction, difficulties in controlling and organizing movements. The most affected spheres were praxis (motor awkwardness, fine motor disorders of the hands) and speech.Conclusion. The proposed hypothesis that the teratogenic effect of taking AEDs may result in unevenness or delay in developing mental functions in a child was confirmed.